Trends and determinants of laboratory specimen rejection rates at Debre Markos comprehensive specialized hospital in Ethiopia - Bewket Mesganaw; Ketema Misganaw; Mekuriaw Belayneh (Scientific Reports)
Abstract Clinical laboratory errors can be classified into pre-analytical, analytical, and post-analytical phases. The majority of laboratory errors originate from the manually intensive activities of the pre-analytical phase, primarily those related to the collection, handling, transportation, preparation, and storage of diagnostic specimens. This study aimed to analyze trends and causes of laboratory specimen rejection among referred diagnostic tests over four years (2020–2023) at Debre Markos comprehensive specialized hospital in Ethiopia. A document review was conducted at Debre Markos Comprehensive Specialized Hospital Laboratory. Specimens tested for viral load for HIV, CD4 count for HIV monitoring, GeneXpert for Mycobacterium tuberculosis, and Early Infant Diagnosis for HIV were included. Finally, statistical analysis was performed using SPSS version 22.0 software. Among 35,673 submitted specimens, 560 (1.57%) were rejected. Annual rejection rates decreased from 2.30% in 2020 to 1.26% in 2023. The most rejected specimens were for CD4 testing (5.41%), and the least for GeneXpert (0.20%). Hemolysis (28.6%) and insufficient volume (22.5%) were the top reasons for rejection. In conclusion, although the trends of laboratory specimen rejection rates among referred specimens was gradually improved from 2020 to 2023, still needs more interventions until it meets to the standard specimen rejection rate of 0.3%.